The Rise and Fall of the Privatized Pension System in Chile An International Perspective. - Solimano, Andrés (Anthem Press, 2021)
'The Rise and Fall of the Privatized Pension System in Chile' analyses the Chilean experience with a privatised pension system and examines its impact on pension levels for the ageing population, differences in benefits across different groups, impact on local capital markets, savings redistribution to big corporations and foreign countries, and high profit rates for pension fund managing companies.